Combined Aerobic and Resistance Training Increases Stretch- Shortening Cycle Potentiation and Walking Economy in Postmenopausal Women - Singh, Harshvardhan; Carter, Stephen J.; Mathis, Shannon L.; Bryan, David R.; Koceja, David M.; McCarthy, John P.; Hunter, Gary R. (Frontiers in Physiology, 2019)
Purpose Secondary analyses were performed to test whether combined aerobic and resistance training altered walking economy (i.e., net oxygen uptake) and/or stretch-shortening cycle potentiation (SSCP). A further objective was to determine if walking economy and SSCP were related before or after training. Methods Ninety-two postmenopausal women were enrolled wherein 76 completed 16 weeks of supervised aerobic and resistance training. Participants were randomized to one of three training groups based on frequencies: (a) 1 d⋅wk–1 (n = 23); (b) 2 d⋅wk–1 (n = 30) or; (c) 3 d⋅wk–1 (n = 23). Following assessments were performed at baseline and post-training. Indirect calorimetry was used to measure maximal oxygen uptake (<inline-graphic xlink:href="fphys-10-01472-i002.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />) and walking economy (submaximal <inline-graphic xlink:href="fphys-10-01472-i001.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" /> – resting <inline-graphic xlink:href="fphys-10-01472-i001.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" /> = net <inline-graphic xlink:href="fphys-10-01472-i001.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />) during a graded exercise test and steady-state treadmill task, respectively. SSCP was determined by measuring the difference between a concentric (CO) and counter-movement (CM) leg press throw. Results <inline-graphic xlink:href="fphys-10-01472-i002.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />, walking economy, CO and CM velocity were significantly improved (p < 0.05) for all training groups, however; no time by group interactions were observed. Paired t-tests revealed participants exercise training 2 d⋅wk–1 exhibited a significant time effect for SSCP (+0.04 ± 0.09 ms–1; p = 0.03). At baseline, multiple linear regression showed a negative relationship between walking net <inline-graphic xlink:href="fphys-10-01472-i001.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" /> and SSCP (r = −0.22; p < 0.04) adjusted for relative proportion of <inline-graphic xlink:href="fphys-10-01472-i002.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />. No such relationship was found post-training. Conclusion Among older postmenopausal women, our results indicate that irrespective of frequency of training, 16 weeks of combined aerobic and resistance exercise training increased ease of walking and economy. Additionally, only participants exercising 2 d⋅wk–1 exhibited significant improvement in SSCP.